The impact of regulatory frameworks on sustainable digital financial practices: Evidence from financial statement indicators in industrial firms - Maytham Abed Kadhim; Bushra Hassan Mohamed El-Toby; Fadhil Hussein Abbas (Heritage and Sustainable Development)
This research explores how regulatory models contribute to sustainable digital financial transformation among industrial firms listed on global stock exchanges between 2015 and 2023. Drawing on quantitative data from company annual reports, it tests three hypotheses: the direct impact of regulatory quality, the mediating role of digital investment, and the moderating effect of firm size. The findings indicate that stronger regulatory environments are positively associated with sustainable financial practices. Digital investment partially mediates this relationship, suggesting that effective regulations encourage firms to upgrade their digital infrastructure, leading to improved long-term performance. The regulatory impact is more pronounced in larger firms due to their greater resources, technological capabilities, and compliance systems. The study concludes that strong regulatory regimes act not just as compliance mechanisms but as institutional enablers of digital transformation and financial transparency. Practical recommendations are offered to help policymakers, regulators, and stakeholders align regulation with innovation and firm capacity to promote sustainable digital progress.